ORAL MANIFESTATIONS IN CHILDREN UNDERGOING HEMODIALYSIS: A COMPREHENSIVE REVIEW OF CLINICAL FEATURES AND PATHOGENETIC MECHANISMS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Children with chronic kidney disease (CKD) undergoing hemodialysis are at high risk of developing oral complications due to systemic metabolic, immunological, and salivary alterations. Oral manifestations in this population are diverse and often underdiagnosed. To analyze the prevalence, clinical features, and pathogenetic mechanisms of oral manifestations in children undergoing hemodialysis. A comprehensive literature review was conducted focusing on studies related to oral health in pediatric CKD patients. Particular attention was given to dental hard tissue lesions, salivary changes, mucosal alterations, and periodontal conditions. Children undergoing hemodialysis commonly present with enamel hypoplasia, dental caries, xerostomia, gingival inflammation, and mucosal lesions. These manifestations are strongly associated with disturbances in mineral metabolism, salivary dysfunction, immune impairment, and uremic toxicity. Oral manifestations in children undergoing hemodialysis reflect systemic pathological processes and require an integrated diagnostic and therapeutic approach. Early identification and multidisciplinary management are essential to improve oral and overall health outcomes.